Determinants of Farmers’ Participation in the Management of Smallholder Irrigation Schemes in Kwazulu-Natal Province, South Africa - Phali, Lerato; Mudhara, Maxwell; Ferrer, Stuart; Makombe, Godswill (Journal of Economics and Behavioral Studies, 2021)
Participatory Irrigation Management is an important concept in the management of water resources. It fosters collective responsibility and rule compliance, the lack of which creates a weak environment for sustainable water use. This study adopted Principal Components Analysis and Structural Equation Modelling to evaluate the determinants of farmer’s participation in the management of four smallholder irrigations schemes in KwaZulu-Natal Province, South Africa. The selected schemes, Ndumo, Makhathini Flats, Mooi River and Tugela Ferry, are representative of the general management and farmer activities in smallholder irrigation schemes in the country. The study considered household data from 341 irrigators and found that those who participated in regulation and control management activities of SIS also participate in information sharing activities. The results show that agricultural training, land tenure security, credit access and co-operative membership positively influence farmers’ participation in decision making. Additionally, irrigation water adequacy positively influences farmer’s participation in making financial contributions in the schemes. The study recommends that better land agreements that, would improve the security of tenure should be put in place to foster farmer participation. Farmers should receive agricultural and irrigation training to increase the likelihood of participating in the management of irrigation schemes.